2020
DOI: 10.1038/s41467-020-16138-3
|View full text |Cite
|
Sign up to set email alerts
|

Fasting mimicking diet as an adjunct to neoadjuvant chemotherapy for breast cancer in the multicentre randomized phase 2 DIRECT trial

Abstract: Breast Cancer Research Group (BOOG) 16, * Short-term fasting protects tumor-bearing mice against the toxic effects of chemotherapy while enhancing therapeutic efficacy. We randomized 131 patients with HER2-negative stage II/III breast cancer, without diabetes and a BMI over 18 kg m −2 , to receive either a fasting mimicking diet (FMD) or their regular diet for 3 days prior to and during neoadjuvant chemotherapy. Here we show that there was no difference in toxicity between both groups, despite the fact that de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
248
1
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(276 citation statements)
references
References 24 publications
14
248
1
13
Order By: Relevance
“…Unfortunately, the study was prematurely interrupted because a pre-planned interim analysis showed a lower-than-anticipated pCR rate in the study population, as well as poor patient adherence to the proposed FMD regimen 1 . In addition, the FMD did not provide evident clinical advantages, neither in terms of reduction of AEs (the primary endpoint of the phase II trial) nor in terms of increased pCR rates (the primary endpoint of the phase III trial) 1 . Of note, triple-negative breast cancer (TNBC) patients, who are much more likely to undergo pCR during preoperative ChT 6 , were significantly more represented in the FMD arm than in the control arm (21.5% vs. 10.9%).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the study was prematurely interrupted because a pre-planned interim analysis showed a lower-than-anticipated pCR rate in the study population, as well as poor patient adherence to the proposed FMD regimen 1 . In addition, the FMD did not provide evident clinical advantages, neither in terms of reduction of AEs (the primary endpoint of the phase II trial) nor in terms of increased pCR rates (the primary endpoint of the phase III trial) 1 . Of note, triple-negative breast cancer (TNBC) patients, who are much more likely to undergo pCR during preoperative ChT 6 , were significantly more represented in the FMD arm than in the control arm (21.5% vs. 10.9%).…”
mentioning
confidence: 99%
“…The main cause of lack of adherence to the experimental diet was dislike of specific components of the FMD, which consisted of a plant-based, standardized kit providing~1200 kcal on day 1 and~200 kcal on days 2-4 1 . Alternative FMD regimens, including schemes containing fresh foods, could be associated with better patient compliance, thus potentially resulting in higher antitumor activity 10 .…”
mentioning
confidence: 99%
“…La evidencia reportada está basada en diseños de estudios de baja evidencia científica: reportes y series de casos, estudios observacionales y pocos estudios clínicos. El tamaño de la muestra es pequeño en la mayoría de los casos, desde 1 persona hasta 129 pacientes, y con diferentes objetivos en la implementación de la DC (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) . Un punto a resaltar es la dificultad de la adherencia a la dieta, así como los periodos de seguimiento.…”
Section: Evidencia Del Uso De La Dieta Cetogénica En Pacientes Con Cáunclassified
“…En los tres casos no reportan efectos adversos. La evidencia más basta surge de tres estudios clínicos realizados en glioblastoma, tumores ginecológicos y cáncer de mama (31,38,39) . De estos, 17 de 20 pacientes con glioblastoma accedieron a realizar la DC entre 6 y 8 semanas.…”
Section: Tabla 2 Estudios En Humanos Que Reportan El Efecto De La DIunclassified
See 1 more Smart Citation